Pengembangan Aktivitas Dakwah Majelis Taklim Al-Karim Latifah di Era Digital: Studi Kualitatif tentang Diversifikasi Program dan Kemandirian Kelembagaan - Anggi Nanda Fadillah; Rendi Sahputra Hasibuan; Athaya Raisa; Fitroh Romodhin Syahputra Lombu; Hendra Kurniawan (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the development of Majelis Taklim activities in attracting congregants to continuously participate in da'wah programs amid the rapid advancement of digital technology. The shift in society’s da'wah consumption patterns toward social media presents significant challenges for Majelis Taklim as a non-formal religious institution. This research employed a qualitative method with a descriptive approach and was conducted in Indonesia. Data were collected through observation, in-depth interviews, and documentation involving Majelis Taklim administrators and congregants. The findings indicate that activity development is implemented through the diversification of da'wah programs, including thematic religious studies, social and charitable activities, congregational empowerment, and the utilization of digital media as a medium of da'wah. Notably, the inclusivity of donors and the absence of financial dependency on a single funding source emerge as distinctive strengths that support the sustainability of these activities. These strategies have proven effective in increasing congregational participation and expanding the reach of da'wah. Through adaptive and responsive activity management aligned with congregational needs, Majelis Taklim remains resilient and relevant in addressing the challenges of da'wah in the digital era.